2004
DOI: 10.1074/jbc.m405007200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ras-Ral Pathway Attenuates p53-independent DNA Damage G2 Checkpoint

Abstract: Earlier we have found that in p53-deficient cells the expression of activated Ras attenuates the DNA damageinduced arrest in G 1 and G 2 . In the present work we studied Ras-mediated effects on the G 2 checkpoint in two human cell lines, MDAH041 immortalized fibroblasts and Saos-2 osteosarcoma cells. The transduction of the H-Ras mutants that retain certain functions (V12S35, V12G37, and V12C40 retain the ability to activate Raf or RalGDS or phosphatidylinositol 3-kinase, respectively) as well as the activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 68 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…Earlier, we reported that the rate of Ras-induced mutagenesis is higher in p53-deficient cells as compared with isogenic cells expressing functional p53 (11). In part, the synergy in the induction of chromosome instability by oncogenic RAS in the p53-null background is explained by the ability of Ras to attenuate the p53-independent components of the DNA damage-induced G 1 and G 2 phase checkpoints (11,16). In the present study, we found a connection between up-regulated ROS and inhibited expression of sestrin family genes, which might represent an additional factor enhancing Ras-induced mutagenesis in p53-deficient cells.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Earlier, we reported that the rate of Ras-induced mutagenesis is higher in p53-deficient cells as compared with isogenic cells expressing functional p53 (11). In part, the synergy in the induction of chromosome instability by oncogenic RAS in the p53-null background is explained by the ability of Ras to attenuate the p53-independent components of the DNA damage-induced G 1 and G 2 phase checkpoints (11,16). In the present study, we found a connection between up-regulated ROS and inhibited expression of sestrin family genes, which might represent an additional factor enhancing Ras-induced mutagenesis in p53-deficient cells.…”
Section: Discussionmentioning
confidence: 95%
“…23; provided by J. Downward, Cancer Research UK, London, United Kingdom); pLXSN-neo/RalA-V23 with constitutively active V23 RalA mutant and lentiviral pLV-CMV/RalA-N28 expressing dominant-negative N28 RalA mutant (16); and lentiviral pLSLP vectors bearing short hairpin RNAs (shRNA) against p53 or human SESN1 and SESN2 genes (21,24). Complementary 60-bp hairpin oligonucleotides containing 19-nucleotide regions corresponding to the human SESN3 gene (5 ¶-GACGAGGAGAAGAGCATTT-3 ¶ and 5 ¶-CCAGAGAGAGATCCAGAAA-3 ¶) were designed according to siRNA-scale algorithm 5 and cloned into pLSLP vector for shRNA, as described earlier (24).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exocyst complexes are bound to vesicles and are supposed to participate in vesicle trafficking and tethering to the plasma membrane. Globally, Ral appears to be a regulator of vesicle trafficking with consequences on cell proliferation, cell fate, and cell signaling (2,13,17,23,30,41).…”
mentioning
confidence: 99%